Process Development for Canning of White Sardine (Kowala coval) - ]eyasekaran, G.; Saralaya, K.V. (Fishery Technology, 2025)
The suitability of canning white sardine (Kowala coval) was studied. The canning procedures of white sardines in natural pack, oil and brine were standardised. Blanching the product in saturated brine at room temperature for 6 min, precooking the product for 45 min in steam at 100Â°C and sterilisation at l15.6Â°C for 75 min yielded a canned product with good organoleptic quality. The results of heat penetration studies are discussed. High temperature and prolonged cooking resulted in a product with brokem meat. Oil packed fish was organoleptically better than natural or brine packed product.